ANALYSIS STUDY THROUGH MATHEMATICA 5.1 SIMULATION PROGRAM IN DETERMINING THE DENSITY AND POROSITY OF CORDIERITE CERAMICS - Juliandi Siregar; M Gade; Khairiah Khairiah; Shinta Marito Siregar (Universitas Islam Negeri Sumatera Utara Medan, 2019)
The research conducted was an experiment with a computational simulation design using the Wolfram Mathematica 5.1 program to view and analyze physical characteristics (density and porosity) of Cordierite Ceramics. The involvement of advanced computers in research will connect the theories and experiments that have been accepted as one of the methods of material research and development. The research variables in this simulation are sintering temperatures of 1200, 1250, 1300, and 1350 °C mixed with wood powder by 20% by weight. The parameters of this study are density and porosity. The simulation results show that with a composition of 20% wood powder and sintering temperature of 1300 °C the density values of 0.97 g/cm3 and porosity of 60.11% are the best conditions that are close to the literature. By comparing the results of simulations and experiments, it can be concluded that through simulation analysis of density and porosity, constant changes can be obtained due to a constant increase in sintering temperature and it can also be analyzed with a smaller temperature increase interval.Keywords: Cordierite Ceramics, Density, Porosity, and Wolfram Mathematica.